2022
DOI: 10.3390/s22228770
|View full text |Cite
|
Sign up to set email alerts
|

Application of Patient Reported Outcome Measures in Cochlear Implant Patients: Implications for the Design of Specific Rehabilitation Programs

Abstract: Introduction: Cochlear implants (CI) have been developed to enable satisfying verbal communication, while music perception has remained in the background in both the research and technological development, thus making CI users dissatisfied by the experience of listening to music. Indications for clinicians to test and train music abilities are at a preliminary stage compared to the existing and well-established hearing and speech rehabilitation programs. The main aim of the present study was to test the utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Elderly individuals often decline a second bilateral implant due to potential side effects from additional surgery. Research aligns with the trend of this case report, showing that two cochlear implants (Cis) helped to enhance subjective satisfaction with hearing ability and actively making music but also improved music perception in general and the health-related quality of life when the results of the SSQ-B are considered [13,26]. While uncertainty exists about the long-term impact of music training on speech perception while listening to music [25], the CI user of this study had a better audiometric threshold, the health-related quality of life as well as music perception improved, and actively participating in challenging tasks as playing instruments and singing was possible.…”
Section: Discussionsupporting
confidence: 77%
“…Elderly individuals often decline a second bilateral implant due to potential side effects from additional surgery. Research aligns with the trend of this case report, showing that two cochlear implants (Cis) helped to enhance subjective satisfaction with hearing ability and actively making music but also improved music perception in general and the health-related quality of life when the results of the SSQ-B are considered [13,26]. While uncertainty exists about the long-term impact of music training on speech perception while listening to music [25], the CI user of this study had a better audiometric threshold, the health-related quality of life as well as music perception improved, and actively participating in challenging tasks as playing instruments and singing was possible.…”
Section: Discussionsupporting
confidence: 77%
“…Both objective and subjective evaluations are utilized to measure the effectiveness of these rehabilitation methods. Notably, subjective evaluations have been shown to correlate with improvements in the quality of life, as indicated by Frosolini et al [ 23 ] in their observational study on patient-reported outcome measures in cochlear implant patients.…”
Section: Discussionmentioning
confidence: 99%
“…The expected effect size was informed by previous data and expert consultation [23], representing the minimum clinically significant difference we aimed to detect between the intervention and control groups. The standard deviation was based on historical data from similar patient populations [24]. Utilizing these parameters, we employed the standard formula for comparing two means in a two-sided test, accounting for equal variance and sample size in both groups.…”
Section: Statisticsmentioning
confidence: 99%